2006
DOI: 10.1103/physrevb.73.064104
|View full text |Cite
|
Sign up to set email alerts
|

Construction, assessment, and application of a bond-order potential for iridium

Abstract: A tight-binding based bond-order potential (BOP) has been constructed for the fcc transition metal iridium that includes explicitly only d orbitals in the evaluation of the total energy. We show that hybridization between the nearly free electron sp band and the unsaturated covalently bonded d orbitals is important in determining the relative stabilities of the close-packed structures and that this effect can be accurately captured through the use of a central force term. The BOP is found to provide an excelle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 58 publications
0
33
0
Order By: Relevance
“…4 results for the hcp structures because they almost coincide with those for the fcc structure and are difficult to discern.͒ Figures 4͑a͒ and 4͑b͒ show that not only is the bcc structure most stable in the whole range of investigated volumes but that both BOP parametrizations reproduce well the DFT results for the fcc, hcp, and sc structures even though the only fitted quantities were the cohesive energy and elastic moduli of the bcc structure at its equilibrium volume. Similarly as in the case of Mo 58 and Ir, 59 the transferability of BOP's to the A15 structure is less satisfactory and the energy of this structure is overestimated when compared with ab initio results. In order to gain an insight into the origin of this discrepancy, we separated the structural energy differences of the three lowest-energy structures, calculated at bcc equilibrium volume per atom, into two parts: the bond contribution E bond , shown in Fig.…”
Section: A Alternative Crystal Structuresmentioning
confidence: 93%
See 2 more Smart Citations
“…4 results for the hcp structures because they almost coincide with those for the fcc structure and are difficult to discern.͒ Figures 4͑a͒ and 4͑b͒ show that not only is the bcc structure most stable in the whole range of investigated volumes but that both BOP parametrizations reproduce well the DFT results for the fcc, hcp, and sc structures even though the only fitted quantities were the cohesive energy and elastic moduli of the bcc structure at its equilibrium volume. Similarly as in the case of Mo 58 and Ir, 59 the transferability of BOP's to the A15 structure is less satisfactory and the energy of this structure is overestimated when compared with ab initio results. In order to gain an insight into the origin of this discrepancy, we separated the structural energy differences of the three lowest-energy structures, calculated at bcc equilibrium volume per atom, into two parts: the bond contribution E bond , shown in Fig.…”
Section: A Alternative Crystal Structuresmentioning
confidence: 93%
“…V͑R ij ͒ is a pair potential and, similarly as in previous studies, [58][59][60]81 it is taken as a sum of cubic splines:…”
Section: Bop Formalism and Parametrizationmentioning
confidence: 99%
See 1 more Smart Citation
“…52 The fcc lattice is then completely unstable, and actually the bcc structure is found to be more stable for nearly filled d bands, when performing total energy calculations. 53,54,55 Similarly the cohesive energies are much too low.…”
Section: Transition Metalmentioning
confidence: 99%
“…14) We have therefore showed that the environmentally dependent bond-order potentials describing correctly not only bonding character but also elastic Cauchy relation in fcc-Ir, have predicted very well planar defect behavior. The latter is crucial for investigating mechanical properties in metals and in particular the origin of brittleness in iridium.…”
Section: à2mentioning
confidence: 99%